The future of construction materials research and the seventh UN Millennium. Development Goa l: a few insights - Pacheco-Torgal, F. (2013)
Although the unsustainability of the human civilization has been recognized long ago, little has ever been done to change it. During the last century, materials use increased 8-fold and as a result Humanity currently uses almost 60 billion tons (Gt) of materials per year. The construction industry alone consumes more raw materials than any other economic activity. However, research on construction materials still is excessively focused on their mechanical properties with minor concerns regarding environmental considerations. In September of 2000 189 UN member states signed the Millennium Development Goals (MDGs), in which the seventh goal is related to environmental sustainability. This is a cornerstone event of paramount significance. However, research in the field of the built environment especially on the field of construction materials still seems unable to recognize its importance. This paper provides some insights on future construction materials research priorities in the context of the seventh MDG. It reviews publication patterns on the field of construction materials highlighting investigations gaps and misdirected research lines. It addresses the importance of nano and biotech hot areas and briefly analyzes the gap between research and market use.